Protuberant Fibro-Osseous Lesion of the Temporal Bone: “Bullough Bump”—Multimodality Imaging Case Series and Literature Review - Shekhrajka, N.; Shatzkes, D.R.; Dean, K.E.; Smithgall, M.C.; Moonis, G. (American Journal of Neuroradiology, 2021)
SUMMARY: A handful of cases of protuberant fibro-osseous lesions of the temporal bones have been described in the literature to date, with primary focus on the pathologic features. Here we review 3 cases of pathology-proved protuberant fibro-osseous lesions of the temporal bone and include a literature review with a focus on the imaging features. While rare, these lesions have near-pathognomonic imaging features defined by a location at the cortex of the outer table of the temporal bone at the occipitomastoid suture, lack of involvement of the underlying marrow, variable mineralization, and MR signal characteristics atypical of a chondroid lesion. One case in this series was FDG-avid and had occasional mitotic features, possibly reflecting an aggressive variant. Neuroradiologists should be familiar with this benign diagnosis to aid in timely identification and avoid unnecessary additional imaging.FDfibrous dysplasiaPFOLTprotuberant fibro-osseous lesion of the temporal bone